2012
DOI: 10.4111/kju.2012.53.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Effect of Distance from Skin to Stone by Computed Tomography Scan on the Extracorporeal Shock Wave Lithotripsy Stone-Free Rate of Renal Stones

Abstract: PurposeTo determine whether the distance from skin to stone, as measured by computed tomography (CT) scans, could affect the stone-free rate achieved via extracorporeal shock wave lithotripsy (ESWL) in renal stone patients.Materials and MethodsWe retrospectively reviewed the records 573 patients who had undergone ESWL at our institution between January 2006 and January 2010 for urinary stones sized from about 5 mm to 20 mm and who had no evidence of stone movement. We excluded patients with ureteral catheters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 18 publications
1
29
1
2
Order By: Relevance
“…The successful group was defined as individuals who are free from stone in CT scan or radiography for six weeks after ESWL and unsuccessful group was determined as remaining particles of stone after six weeks of ESWL. The results of this study showed that the SSD influenced the results of ESWL (14). These findings are similar to our study too.…”
Section: Discussionsupporting
confidence: 92%
“…The successful group was defined as individuals who are free from stone in CT scan or radiography for six weeks after ESWL and unsuccessful group was determined as remaining particles of stone after six weeks of ESWL. The results of this study showed that the SSD influenced the results of ESWL (14). These findings are similar to our study too.…”
Section: Discussionsupporting
confidence: 92%
“…In some studies, however, no significant correlation was found between Hounsfield unit value and ESWL outcome [6, 11]. In our study, Hounsfield units of stone was a strong predictor of success of the procedure.…”
Section: Discussioncontrasting
confidence: 61%
“…Park BH, et al described significant influence of SSD for ESWL in renal stones [6]. Müllhaupt, et al studied the effect of SSD on ureteral stone fragmentation and described its significance.…”
Section: Discussionmentioning
confidence: 99%
“…The increased use of computed tomography (CT) to assess urinary calculi has provided information on some stone parameters, such as mean stone density (MSD) and stone volume (SV), that could be used to predict treatment outcomes after SWL [ 1 , 2 ]. Among the various stone parameters, skin-to-stone distance (SSD) is another factor that might be able to predict the results of treatment, although its role in the prediction of treatment outcomes is still controversial [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Because the shock wave (SW) path passes through various tissues with different compositions and densities, transmission of the SW along these different tissue planes may lead to energy loss and hence affect treatment outcome [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%